Analysis of Social-Emotional Development Through Collaborative Learning of Informatics Subjects for High School Students - Nahila Sibta Nadia; Aris Budianto; Basuki Sri Wibowo (Journal of Informatics and Vocational Education, 2025)
This study aims to analyze the implementation of collaborative learning based on crossword puzzles and its relationship to the social-emotional development of class X E5 students. This study uses a qualitative descriptive approach and data collection through observation and documentation during the learning process. This study shows that the implementation of collaborative learning strategies based on crossword puzzles can increase learning interactions actively and optimally. This is seen from the increase in empathy, self-confidence, communication, interactivity, and the ability to work together in groups. This study shows that the integration of collaborative learning with crossword puzzles not only supports the understanding of computer network concepts but also plays a role in the social-emotional development of students. Thus, collaborative learning based on crossword puzzles can be an innovative learning strategy in informatics subjects that is holistically oriented.